BEES AND THEIR RELEVANT IMPORTANCE IN THE POLLINATION PROCESS - Pereira da Silva, Luciano; Edemar (Revista Interface Tecnológica, 2022)
Agriculture has gone through many phases, from urban development to deforestation, through the exacerbated use of chemicals and human activities, which have brought threats to biodiversity as the main consequences, impacting negatively especially when we talk about the population of pollinators. , from which they did not find enough resources to feed and nest. It is of great importance to emphasize that pollination is a natural and mechanical process. Where bees are essential and indispensable pollinating agents, in view of this, the preservation of their species is of great importance, a fact that has not happened in recent times, generating great environmental concern. Thus, the objective of this study is to highlight the importance of bees in the pollination process, demonstrating the causes of death of these insects and their negative impacts on agriculture. This article presents a narrative literature review with consultations in articles and documents that focus on the theme of this study. The literature makes it clear that bees indicate environmental quality and the loss of this insect represents an imminent threat to the health of existing ecosystems. Strategies need to be created to prevent the loss of bees from becoming a threat.